Evaluation of Prothrombin and Activated Partial Thromboplastin Time in Patients with Diabetes Mellitus - Halima Algadi (AlQalam Journal of Medical and Applied Sciences, 2024)
Diabetes mellitus (DM) is a metabolic disease accompanied by high blood glucose due to a defect in insulin secretion, insulin activity, or both. High blood glucose levels may lead to serious damage to some organs of the body, mainly blood vessels and nerves. Therefore, this study was conducted to evaluate prothrombin time (PT) and activated partial thromboplastin time (APTT) in diabetic patients. 100 venous blood samples were collected from diabetic patients attending the diabetes clinic in Sebha. Of them, 57 were males and 53 were females, and their ages ranged between 15-88 years. out of 100, 48 Were treated with insulin-regulating tablets and 52 Were treated with insulin injections. 34 blood samples were collected from healthy people (15 females and 19 males). They were used as a control group, aged between 14-55 years. 4 ml of venous blood was drawn, and 2 ml was placed in containers containing the anticoagulant sodium citrate to perform the PT and APTT. Place 2 ml of sample in tubes containing sodium fluoride anticoagulant to perform a fasting blood sugar (FBS). Place the tubes in a centrifuge at 3000 rpm to obtain plasma. The results showed the mean of PT in patients was (19.4 ± 3.6), the mean APTT was (35.9 ± 1.5) and the Mean FBS was (229.7 ± 80.39), whereas the mean PT, APTT, and FBS in control were (12.8 ± 1.6), (25.4 ± 2.1), and (91.9 ± 12.5) respectively. there was a significant increase of PT and APTT in patients compared to control (P<0.05), PT and FBS were higher in patients who used insulin injection with significant differences(P<0.05), while no significant differences were in APTT (P > 0.05). The present study observed a statistically significant increase in PT and APTT among patients compared to controls, it would be helpful to incorporate coagulation screening as a routine investigation for the better management of diabetic patients. مرض السكري هو مرض أيضي يصاحبه ارتفاع سكر الدم بسبب خلل في إفراز الأنسولين أو نشاط الأنسولين أو كليهما. قد يؤدي ارتفاع سكر الدم إلى تلف خطير في بعض أعضاء الجسم، وخاصة الاعصاب والأوعية الدموية. أجريت هذه الدراسة لتقييم زمن البروثرومبين وزمن الثرومبوبلاستين الجزئي المنشط لدى مرضى السكري. تم جمع 100 عينة دم وريدي من مرضى السكري المترددين على عيادة السكري في مدينة سبها. كان منهم 57 ذكور و53 اناث، وتراوحت أعمارهم بين 15-88 سنة. من 100، 48 مريض يعالجوا بأقراص تنظيم الأنسولين و52 يعالجوا بحقن الأنسولين. تم جمع 34 عينة دم من أشخاص أصحاء (15 اناث و19 ذكور). كمجموعة ضابطة. كان متوسط زمن البروثرومبين لدى المرضى (19.4 ± 3.6) ثانية، ومتوسط زمن الثرومبوبلاستين الجزئي المنشط كان (35.9 ± 1.5) ثانية، ومتوسط سكر الصيام كان (229 ± 80.4) ميلجرام لكل ديسليتر, بينما كان متوسط زمن البروثرومبين وزمن الثرومبوبلاستين الجزئي المنشط والسكر في المجموعة الضابطة (12.8 ± 1.6)، (25.4 ± 2.1)، (91.9 ± 12.5) على التوالي. كان هناك زيادة ذات دلالة إحصائية في زمن البروثرومبين وزمن الثرومبوبلاستين الجزئي المنشط في المرضى مقارنة بالضوابط، كان زمن البروثرومبين ومستوى السكر أعلى في المرضى الذين استخدموا حقن الأنسولين مع وجود فروق معنوية، لم تكن هناك فروق معنوية في زمن الثرومبوبلاستين الجزئي المنشط، نستخلص من الدراسة الحالية ان هناك زيادة ذات دلاله إحصائيًة في زمن البروثرومبين وزمن الثرومبوبلاستين الجزئي المنشط بين المرضى مقارنة بالضابطة، سيكون من المفيد دمج فحص التخثر كفحص روتيني لتحسين متابعة مرضى السكري